Knowledge and attitude toward depression among healthcare professionals working in Ilu Aba Bor zone, Oromia regional state, Ethiopia, 2021: a cross sectional study - Alemayehu, Yadeta; Girma, Million; Bacha, Lemi; Boka, Kefale; Tarafa, Hunde (Frontiers in Psychiatry, 2023)
Background Depression is the major mental disorder that frequently co-occurs with other physical illnesses, although its detection at primary healthcare is limited. Thus, the purpose of this study is to evaluate health professionals’ knowledge and attitude toward depression and its related factors. Objective To assess knowledge and attitude of healthcare professionals toward people with depression at different health facilities of Ilu Aba Bor zone, Ethiopia, 2021. Methods A cross-sectional study was carried out involving 404 primary healthcare professionals using a systematic random sampling technique in February 2021. Attitude was assessed using depression attitude questionnaires. Epi-data version 3.1 and SPSS version 26 was used for data entry and analysis. The p-values lower than 0.05 were deemed statistically significant. Result In the current study, 30.4% (95% CI; 25.86, 34.94) of the respondents have inadequate knowledge and 29.9% (95% CI; 25.4, 36.8) have negative attitude toward depression. A vast majority (77.7%) of healthcare professionals have never received any kind of training on mental health. Accordingly, contact with the person with mental illness and mental health training were significantly associated with inadequate knowledge. In addition, perceived cause of depression and mental health training were significantly associated with negative attitude. Conclusion According to this study, the magnitude of inadequate knowledge and negative attitude in the diagnosis and treatment of depression is comparably high. Therefore, primary healthcare settings should prioritize raising awareness, promoting positive attitudes, and improving detection and treatment of depression cases.